The Word that Builds: Poetry and Practice at the School of Valparaíso - Andrade, Óscar; Gil, Jaime Reyes (Writingplace, 2018)
This article addresses the case of the School of Architecture and Design at Pontificia Universidad Católica de Valparaíso in Chile, which established an original position in arts and education by exploring the productive relationship between poetry and architecture. The focus of this article is to examine the pivotal presence of poetry in the school’s artistic position and its role in the design and building actions carried out by students and professors, which are an essential trait of its educational approach. The article displays this trajectory from the poetic word to the act of building by discussing a crucial topic raised within inter-nal debates of the School of Valparaíso: the relationship between word and action. While illustrating the role of poetry in the school’s creative practices, the article argues that the poetic word is not instrumentalized as a concrete method or tool in design studio practices, but is present as an underlying element that opens a primordial creative field from which architecture operates. The article aims to contribute to the existing literature by clarifying the role of poetry in the School of Valparaíso’s curriculum, which is a particu- larly unclear aspect surrounded by myths and assumptions. Therefore, this article focuses on the formulation and practice of the ‘poetic act’, its role in the design and building processes of the school projects, and the way in which the professors and students of the School of Valparaíso proceed with their works after the poetic act that takes place at the start of every project. By clarifying these points, we shine a light on the presence of poetry in the articulation of the school’s artistic production and academic structures, locating the relationship between word and action at the centre of the school’s debates, where it remains open and vividly discussed to this day.